2013
DOI: 10.7314/apjcp.2013.14.12.7421
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-19a Predicts Resistance to FOLFOX Chemotherapy in Advanced Colorectal Cancer Cases

Abstract: Background: Colorectal cancer is the fourth most common cancer worldwide and the second leading cause of cancer-related death. FOLFOX is the most common regimen used in the first-line chemotherapy in advanced colorectal cancer, but only half of the patients respond to this regimen and we have almost no clue in predicting resistance in such first-line application. Methods: To explore the potential molecular biomarkers predicting the resistance of FOLFOX regimen as the first-line treatment in advanced colorectal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 42 publications
3
52
0
Order By: Relevance
“…Among them, finding biomarkers for prognosis has long been a hotspot (Huang et al, 2012;Qian et al, 2012;Zhang et al, 2012;Chen et al, 2013;Cui et al, 2013;Dong et al, 2013;Sisik et al, 2013;Wu et al, 2013). Myosins have a well-characterized biological function in using the energy of ATP hydrolysis to move actin filaments to produce muscle force.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, finding biomarkers for prognosis has long been a hotspot (Huang et al, 2012;Qian et al, 2012;Zhang et al, 2012;Chen et al, 2013;Cui et al, 2013;Dong et al, 2013;Sisik et al, 2013;Wu et al, 2013). Myosins have a well-characterized biological function in using the energy of ATP hydrolysis to move actin filaments to produce muscle force.…”
Section: Discussionmentioning
confidence: 99%
“…Despite several genes have being proved that relate to genesis of CRC, the exact mechanisms underlying he development and progression CRC are still poorly understood (Goel and Boland, 2010). Throughout the articles relate to CRC in the journal ACJCP over the past two years, it is not difficult to find that the novel molecular markers with potential of treatment and prognosis have captured more and more attention (Chen et al, 2013;Zhu et al, 2013). Given this consideration, it is imperative to seek out a key gene associated with the progression and pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that pre-therapy plasma miRNAs may serve as non-invasive markers to predict outcome in mCRC patients treated with 5-FU/oxaliplatin chemotherapy [89]. Aberrant elevation of serum miR-19a was also found to predict non-responders to FOLFOX chemotherapy in advanced CRC [90]. Another study identified a distinct serum miRNA expression signature in response to chemotherapy.…”
Section: Micrornas As Non-invasive Biomarkers Of Drug Response In Crcmentioning
confidence: 89%